ListsWorking with Structured Data
Overview
Pairs of Numbers
This declaration can be read: "The one and only way to
construct a pair of numbers is by applying the constructor pair
to two arguments of type nat."
Here are two simple functions for extracting the first and
second components of a pair. The definitions also illustrate how
to do pattern matching on two-argument constructors.
Definition fst (p : natprod) : nat :=
match p with
| pair x y ⇒ x
end.
Definition snd (p : natprod) : nat :=
match p with
| pair x y ⇒ y
end.
Compute (fst (pair 3 5)).
(* ===> 3 *)
Since pairs are used quite a bit, it is nice to be able to
write them with the standard mathematical notation (x,y) instead
of pair x y. We can tell Coq to allow this with a Notation
declaration.
The new pair notation can be used both in expressions and in
pattern matches (indeed, we've actually seen this already in the
Basics chapter, in the definition of the minus function --
this works because the pair notation is also provided as part of
the standard library):
Compute (fst (3,5)).
Definition fst' (p : natprod) : nat :=
match p with
| (x,y) ⇒ x
end.
Definition snd' (p : natprod) : nat :=
match p with
| (x,y) ⇒ y
end.
Definition swap_pair (p : natprod) : natprod :=
match p with
| (x,y) ⇒ (y,x)
end.
Let's try to prove a few simple facts about pairs.
If we state things in a particular (and slightly peculiar) way, we
can complete proofs with just reflexivity (and its built-in
simplification):
Theorem surjective_pairing' : ∀ (n m : nat),
(n,m) = (fst (n,m), snd (n,m)).
Proof.
reflexivity. Qed.
But reflexivity is not enough if we state the lemma in a more
natural way:
Theorem surjective_pairing_stuck : ∀ (p : natprod),
p = (fst p, snd p).
Proof.
simpl. (* Doesn't reduce anything! *)
Abort.
We have to expose the structure of p so that simpl can
perform the pattern match in fst and snd. We can do this with
destruct.
Theorem surjective_pairing : ∀ (p : natprod),
p = (fst p, snd p).
Proof.
intros p. destruct p as [n m]. simpl. reflexivity. Qed.
Notice that, unlike its behavior with nats, destruct
generates just one subgoal here. That's because natprods can
only be constructed in one way.
Exercise: 1 star, standard (snd_fst_is_swap)
Theorem snd_fst_is_swap : ∀ (p : natprod),
(snd p, fst p) = swap_pair p.
Proof.
(* FILL IN HERE *) Admitted.
☐
(snd p, fst p) = swap_pair p.
Proof.
(* FILL IN HERE *) Admitted.
☐
Theorem fst_swap_is_snd : ∀ (p : natprod),
fst (swap_pair p) = snd p.
Proof.
(* FILL IN HERE *) Admitted.
☐
fst (swap_pair p) = snd p.
Proof.
(* FILL IN HERE *) Admitted.
☐
Lists of Numbers
For example, here is a three-element list:
As with pairs, it is more convenient to write lists in
familiar programming notation. The following declarations
allow us to use :: as an infix cons operator and square
brackets as an "outfix" notation for constructing lists.
Notation "x :: l" := (cons x l)
(at level 60, right associativity).
Notation "[ ]" := nil.
Notation "[ x ; .. ; y ]" := (cons x .. (cons y nil) ..).
It is not necessary to understand the details of these
declarations, but in case you are interested, here is roughly
what's going on. The right associativity annotation tells Coq
how to parenthesize expressions involving several uses of :: so
that, for example, the next three declarations mean exactly the
same thing:
Definition mylist1 := 1 :: (2 :: (3 :: nil)).
Definition mylist2 := 1 :: 2 :: 3 :: nil.
Definition mylist3 := [1;2;3].
The at level 60 part tells Coq how to parenthesize
expressions that involve both :: and some other infix operator.
For example, since we defined + as infix notation for the plus
function at level 50,
Notation "x + y" := (plus x y)
(at level 50, left associativity).
the + operator will bind tighter than ::, so 1 + 2 :: [3]
will be parsed, as we'd expect, as (1 + 2) :: [3] rather than 1
+ (2 :: [3]).
(Expressions like "1 + 2 :: [3]" can be a little confusing when
you read them in a .v file. The inner brackets, around 3, indicate
a list, but the outer brackets, which are invisible in the HTML
rendering, are there to instruct the "coqdoc" tool that the bracketed
part should be displayed as Coq code rather than running text.)
The second and third Notation declarations above introduce the
standard square-bracket notation for lists; the right-hand side of
the third one illustrates Coq's syntax for declaring n-ary
notations and translating them to nested sequences of binary
constructors.
A number of functions are useful for manipulating lists.
For example, the repeat function takes a number n and a
count and returns a list of length count where every element
is n.
Notation "x + y" := (plus x y)
(at level 50, left associativity).
Repeat
Fixpoint repeat (n count : nat) : natlist :=
match count with
| O ⇒ nil
| S count' ⇒ n :: (repeat n count')
end.
Fixpoint app (l1 l2 : natlist) : natlist :=
match l1 with
| nil ⇒ l2
| h :: t ⇒ h :: (app t l2)
end.
Actually, app will be used a lot in some parts of what
follows, so it is convenient to have an infix operator for it.
Notation "x ++ y" := (app x y)
(right associativity, at level 60).
Example test_app1: [1;2;3] ++ [4;5] = [1;2;3;4;5].
Proof. reflexivity. Qed.
Example test_app2: nil ++ [4;5] = [4;5].
Proof. reflexivity. Qed.
Example test_app3: [1;2;3] ++ nil = [1;2;3].
Proof. reflexivity. Qed.
Head (with default) and Tail
Definition hd (default:nat) (l:natlist) : nat :=
match l with
| nil ⇒ default
| h :: t ⇒ h
end.
Definition tl (l:natlist) : natlist :=
match l with
| nil ⇒ nil
| h :: t ⇒ t
end.
Example test_hd1: hd 0 [1;2;3] = 1.
Proof. reflexivity. Qed.
Example test_hd2: hd 0 [] = 0.
Proof. reflexivity. Qed.
Example test_tl: tl [1;2;3] = [2;3].
Proof. reflexivity. Qed.
Exercises
Exercise: 2 stars, standard, recommended (list_funs)
Complete the definitions of nonzeros, oddmembers and countoddmembers below. Have a look at the tests to understand what these functions should do.Fixpoint nonzeros (l:natlist) : natlist
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Example test_nonzeros:
nonzeros [0;1;0;2;3;0;0] = [1;2;3].
(* FILL IN HERE *) Admitted.
Fixpoint oddmembers (l:natlist) : natlist
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Example test_oddmembers:
oddmembers [0;1;0;2;3;0;0] = [1;3].
(* FILL IN HERE *) Admitted.
Definition countoddmembers (l:natlist) : nat
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Example test_countoddmembers1:
countoddmembers [1;0;3;1;4;5] = 4.
(* FILL IN HERE *) Admitted.
Example test_countoddmembers2:
countoddmembers [0;2;4] = 0.
(* FILL IN HERE *) Admitted.
Example test_countoddmembers3:
countoddmembers nil = 0.
(* FILL IN HERE *) Admitted.
☐
Exercise: 3 stars, advanced (alternate)
Complete the definition of alternate, which "zips up" two lists into one, alternating between elements taken from the first list and elements from the second. See the tests below for more specific examples.Fixpoint alternate (l1 l2 : natlist) : natlist
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Example test_alternate1:
alternate [1;2;3] [4;5;6] = [1;4;2;5;3;6].
(* FILL IN HERE *) Admitted.
Example test_alternate2:
alternate [1] [4;5;6] = [1;4;5;6].
(* FILL IN HERE *) Admitted.
Example test_alternate3:
alternate [1;2;3] [4] = [1;4;2;3].
(* FILL IN HERE *) Admitted.
Example test_alternate4:
alternate [] [20;30] = [20;30].
(* FILL IN HERE *) Admitted.
☐
Reasoning About Lists
... because the [] is substituted into the
"scrutinee" (the expression whose value is being "scrutinized" by
the match) in the definition of app, allowing the match itself
to be simplified.
Also, as with numbers, it is sometimes helpful to perform case
analysis on the possible shapes (empty or non-empty) of an unknown
list.
Theorem tl_length_pred : ∀ l:natlist,
pred (length l) = length (tl l).
Proof.
intros l. destruct l as [| n l'].
- (* l = nil *)
reflexivity.
- (* l = cons n l' *)
reflexivity. Qed.
Here, the nil case works because we've chosen to define
tl nil = nil. Notice that the as annotation on the destruct
tactic here introduces two names, n and l', corresponding to
the fact that the cons constructor for lists takes two
arguments (the head and tail of the list it is constructing).
Usually, though, interesting theorems about lists require
induction for their proofs.
Micro-Sermon
Induction on Lists
- First, show that P is true of l when l is nil.
- Then show that P is true of l when l is cons n l' for some number n and some smaller list l', assuming that P is true for l'.
Theorem app_assoc : ∀ l1 l2 l3 : natlist,
(l1 ++ l2) ++ l3 = l1 ++ (l2 ++ l3).
Proof.
intros l1 l2 l3. induction l1 as [| n l1' IHl1'].
- (* l1 = nil *)
reflexivity.
- (* l1 = cons n l1' *)
simpl. rewrite → IHl1'. reflexivity. Qed.
Notice that, as when doing induction on natural numbers, the
as... clause provided to the induction tactic gives a name to
the induction hypothesis corresponding to the smaller list l1'
in the cons case. Once again, this Coq proof is not especially
illuminating as a static written document -- it is easy to see
what's going on if you are reading the proof in an interactive Coq
session and you can see the current goal and context at each
point, but this state is not visible in the written-down parts of
the Coq proof. So a natural-language proof -- one written for
human readers -- will need to include more explicit signposts; in
particular, it will help the reader stay oriented if we remind
them exactly what the induction hypothesis is in the second
case.
For comparison, here is an informal proof of the same theorem.
Theorem: For all lists l1, l2, and l3,
(l1 ++ l2) ++ l3 = l1 ++ (l2 ++ l3).
Proof: By induction on l1.
For a slightly more involved example of inductive proof over
lists, suppose we use app to define a list-reversing function
rev:
- First, suppose l1 = []. We must show
([] ++ l2) ++ l3 = [] ++ (l2 ++ l3), - Next, suppose l1 = n::l1', with
(l1' ++ l2) ++ l3 = l1' ++ (l2 ++ l3)
((n :: l1') ++ l2) ++ l3 = (n :: l1') ++ (l2 ++ l3).
n :: ((l1' ++ l2) ++ l3) = n :: (l1' ++ (l2 ++ l3)),
Reversing a List
Fixpoint rev (l:natlist) : natlist :=
match l with
| nil ⇒ nil
| h :: t ⇒ rev t ++ [h]
end.
Example test_rev1: rev [1;2;3] = [3;2;1].
Proof. reflexivity. Qed.
Example test_rev2: rev nil = nil.
Proof. reflexivity. Qed.
Properties of rev
Theorem rev_length_firsttry : ∀ l : natlist,
length (rev l) = length l.
Proof.
intros l. induction l as [| n l' IHl'].
- (* l = *)
reflexivity.
- (* l = n :: l' *)
(* This is the tricky case. Let's begin as usual
by simplifying. *)
simpl.
(* Now we seem to be stuck: the goal is an equality
involving ++, but we don't have any useful equations
in either the immediate context or in the global
environment! We can make a little progress by using
the IH to rewrite the goal... *)
rewrite <- IHl'.
(* ... but now we can't go any further. *)
Abort.
So let's take the equation relating ++ and length that
would have enabled us to make progress and prove it as a separate
lemma.
Theorem app_length : ∀ l1 l2 : natlist,
length (l1 ++ l2) = (length l1) + (length l2).
Proof.
(* WORKED IN CLASS *)
intros l1 l2. induction l1 as [| n l1' IHl1'].
- (* l1 = nil *)
reflexivity.
- (* l1 = cons *)
simpl. rewrite → IHl1'. reflexivity. Qed.
Note that, to make the lemma as general as possible, we
quantify over all natlists, not just those that result from an
application of rev. This should seem natural, because the truth
of the goal clearly doesn't depend on the list having been
reversed. Moreover, it is easier to prove the more general
property.
Now we can complete the original proof.
Theorem rev_length : ∀ l : natlist,
length (rev l) = length l.
Proof.
intros l. induction l as [| n l' IHl'].
- (* l = nil *)
reflexivity.
- (* l = cons *)
simpl. rewrite → app_length, plus_comm.
simpl. rewrite → IHl'. reflexivity. Qed.
For comparison, here are informal proofs of these two theorems:
Theorem: For all lists l1 and l2,
length (l1 ++ l2) = length l1 + length l2.
Proof: By induction on l1.
Theorem: For all lists l, length (rev l) = length l.
Proof: By induction on l.
The style of these proofs is rather longwinded and pedantic.
After the first few, we might find it easier to follow proofs that
give fewer details (which can easily work out in our own minds or
on scratch paper if necessary) and just highlight the non-obvious
steps. In this more compressed style, the above proof might look
like this:
Theorem:
For all lists l, length (rev l) = length l.
Proof: First, observe that length (l ++ [n]) = S (length l)
for any l (this follows by a straightforward induction on l).
The main property again follows by induction on l, using the
observation together with the induction hypothesis in the case
where l = n'::l'. ☐
Which style is preferable in a given situation depends on
the sophistication of the expected audience and how similar the
proof at hand is to ones that the audience will already be
familiar with. The more pedantic style is a good default for our
present purposes---please stick with it for now on exercises.
- First, suppose l1 = []. We must show
length ([] ++ l2) = length [] + length l2, - Next, suppose l1 = n::l1', with
length (l1' ++ l2) = length l1' + length l2.
length ((n::l1') ++ l2) = length (n::l1') + length l2).
- First, suppose l = []. We must show
length (rev []) = length [], - Next, suppose l = n::l', with
length (rev l') = length l'.
length (rev (n :: l')) = length (n :: l').
length ((rev l') ++ [n]) = S (length l')
length (rev l') + length [n] = S (length l').
Search
(* Search rev. *)
Keep Search in mind as you do the following exercises and
throughout the rest of the book; it can save you a lot of time!
If you are using ProofGeneral, you can run Search with C-c
C-a C-a. Pasting its response into your buffer can be
accomplished with C-c C-;.
Theorem app_nil_r : ∀ l : natlist,
l ++ [] = l.
Proof.
(* FILL IN HERE *) Admitted.
Theorem rev_app_distr: ∀ l1 l2 : natlist,
rev (l1 ++ l2) = rev l2 ++ rev l1.
Proof.
(* FILL IN HERE *) Admitted.
Theorem rev_involutive : ∀ l : natlist,
rev (rev l) = l.
Proof.
(* FILL IN HERE *) Admitted.
There is a short solution to the next one. If you find yourself
getting tangled up, step back and try to look for a simpler
way.
Theorem app_assoc4 : ∀ l1 l2 l3 l4 : natlist,
l1 ++ (l2 ++ (l3 ++ l4)) = ((l1 ++ l2) ++ l3) ++ l4.
Proof.
(* FILL IN HERE *) Admitted.
An exercise about your implementation of nonzeros:
Lemma nonzeros_app : ∀ l1 l2 : natlist,
nonzeros (l1 ++ l2) = (nonzeros l1) ++ (nonzeros l2).
Proof.
(* FILL IN HERE *) Admitted.
☐
Exercise: 2 stars, standard (eqblist)
Fill in the definition of eqblist, which compares lists of numbers for equality. Prove that eqblist l l yields true for every list l.Fixpoint eqblist (l1 l2 : natlist) : bool
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Example test_eqblist1 :
(eqblist nil nil = true).
(* FILL IN HERE *) Admitted.
Example test_eqblist2 :
eqblist [1;2;3] [1;2;3] = true.
(* FILL IN HERE *) Admitted.
Example test_eqblist3 :
eqblist [1;2;3] [1;2;4] = false.
(* FILL IN HERE *) Admitted.
Theorem eqblist_refl : ∀ l:natlist,
true = eqblist l l.
Proof.
(* FILL IN HERE *) Admitted.
☐
Sums
Σ_i=1^n i
Σ_i=0^n i = i[i=0] + i[i=1] + i[i=2] + ... + i[i=n-1] + i[i=n] = 0 + 1 + 2 + ... + n-1 + n
Fixpoint sum_natlist (l : natlist) : nat :=
match l with
| nil ⇒ 0
| cons n l' ⇒ n + sum_natlist l'
end.
Fixpoint ones (n : nat) : natlist :=
match n with
| O ⇒ nil
| S n' ⇒ cons 1 (ones n')
end.
Lemma sum_natlist_ones : ∀ n : nat,
sum_natlist (ones n) = n.
Proof.
(* WORKED IN CLASS *)
induction n as [|n' IHn'].
- reflexivity.
- simpl. rewrite → IHn'. reflexivity.
Qed.
Fixpoint odds (n : nat) : natlist :=
match n with
| O ⇒ [1]
| S n' ⇒ 2 × (S n') + 1 :: odds n'
end.
Lemma sum_natlist_odds : ∀ n,
sum_natlist (odds n) = (n+1)*(n+1).
Proof.
(* WORKED IN CLASS *)
intros n. induction n as [|n' IHn'].
- reflexivity.
- simpl. rewrite → IHn'. simpl.
rewrite <- plus_n_Sm. rewrite <- plus_n_Sm. rewrite <- plus_n_Sm.
rewrite <- plus_n_O. rewrite <- plus_n_O.
simpl.
rewrite <- plus_n_Sm. rewrite <- plus_n_Sm.
rewrite <- plus_n_Sm.
rewrite <- plus_assoc.
assert (n' × S (S n') = n' + n' × S n').
{ rewrite <- mult_n_Sm. rewrite plus_comm. reflexivity. }
rewrite → H.
reflexivity.
Qed.
Your choices in proofs matter a lot! You might need to do
substantially more work if you pick a hard way to go.
The bad news is that there's no easy rule for predicting which way
will be harder or easier. But the good news is that you'll improve
a lot with mindful practice.
Lemma sum_natlist_odds' : ∀ n,
sum_natlist (odds n) = (n+1)*(n+1).
Proof.
intros n. induction n as [|n' IHn'].
- reflexivity.
- rewrite plus_comm.
assert ((1 + S n') × (1 + S n') = 1 + S n' + S n' + (S n') × (S n')).
{ rewrite <- mult_n_Sm. rewrite plus_comm.
simpl. rewrite <- plus_n_Sm. rewrite <- plus_n_Sm.
rewrite <- plus_n_Sm. rewrite <- plus_n_Sm.
rewrite <- plus_n_Sm. rewrite → plus_assoc.
rewrite → plus_assoc. rewrite → plus_assoc.
simpl. reflexivity. }
rewrite H.
assert (S n' × S n' = (n' + 1) × (n' + 1)).
{ rewrite plus_comm. reflexivity. }
rewrite H0.
rewrite <- IHn'.
simpl. rewrite <- plus_n_Sm.
rewrite <- plus_n_O.
rewrite <- plus_n_O.
simpl. reflexivity.
Qed.
Exercise: 2 stars, standard, recommended (sum_natlist_ntoone)
Show the following property, or, as it's better known:Σ_i=0^n i = 0 + 1 + 2 + 3 + ... + n-1 + n = n*(n+1)/2
Fixpoint ntoone (n:nat) : natlist :=
match n with
| 0 ⇒ nil
| S n' ⇒ n :: (ntoone n')
end.
Lemma sum_natlist_ntoone : ∀ n : nat,
2 × sum_natlist (ntoone n) = n × (n + 1).
Proof.
(* FILL IN HERE *) Admitted.
☐
match n with
| 0 ⇒ nil
| S n' ⇒ n :: (ntoone n')
end.
Lemma sum_natlist_ntoone : ∀ n : nat,
2 × sum_natlist (ntoone n) = n × (n + 1).
Proof.
(* FILL IN HERE *) Admitted.
☐
Exercise: 3 stars, standard (sum_natlist_rev)
You may have noticed that we didn't exactly prove the sum we wanted to. First, we proved2 × Σ_i=1^n i = n*(n+1)
Σ_i=1^n i = n*(n+1)/2.
Lemma sum_natlist_rev : ∀ l : natlist,
sum_natlist l = sum_natlist (rev l).
Proof.
(* FILL IN HERE *) Admitted.
☐
Σ_i=1^n n = n×n.
Lemma sum_natlist_repeat_n : ∀ n : nat,
sum_natlist (repeat n n) = n × n.
Proof.
induction n as [|n' IHn'].
- reflexivity.
- (* our IH won't help _at all_! *)
Abort.
sum_natlist (repeat n n) = n × n.
Proof.
induction n as [|n' IHn'].
- reflexivity.
- (* our IH won't help _at all_! *)
Abort.
What went wrong? Since n appeared more than once in the
proposition we were proving---our goal---when we went by
induction, we updated n in both cases.
The solution here is generalizing the induction hypothesis: we
prove a slightly more general property that will imply the one we
want. Here, it's a simple generalization: separate out the number
we're adding and the number of times we add it to itself.
Exercise: 2 stars, standard (sum_natlist_repeat_n)
Lemma sum_natlist_repeat_n_m : ∀ n m : nat,
sum_natlist (repeat n m) = n × m.
Proof.
(* FILL IN HERE *) Admitted.
Lemma sum_natlist_repeat_n : ∀ n : nat,
sum_natlist (repeat n n) = n × n.
Proof.
(* FILL IN HERE *) Admitted.
☐
sum_natlist (repeat n m) = n × m.
Proof.
(* FILL IN HERE *) Admitted.
Lemma sum_natlist_repeat_n : ∀ n : nat,
sum_natlist (repeat n n) = n × n.
Proof.
(* FILL IN HERE *) Admitted.
☐
Options
Fixpoint nth_bad (l:natlist) (n:nat) : nat :=
match l with
| nil ⇒ 42 (* arbitrary! *)
| a :: l' ⇒ match eqb n O with
| true ⇒ a
| false ⇒ nth_bad l' (pred n)
end
end.
This solution is not so good: If nth_bad returns 42, we
can't tell whether that value actually appears on the input
without further processing. A better alternative is to change the
return type of nth_bad to include an error value as a possible
outcome. We call this type natoption.
We can then change the above definition of nth_bad to
return None when the list is too short and Some a when the
list has enough members and a appears at position n. We call
this new function nth_error to indicate that it may result in an
error.
Fixpoint nth_error (l:natlist) (n:nat) : natoption :=
match l with
| nil ⇒ None
| a :: l' ⇒ match eqb n O with
| true ⇒ Some a
| false ⇒ nth_error l' (pred n)
end
end.
Example test_nth_error1 : nth_error [4;5;6;7] 0 = Some 4.
Proof. reflexivity. Qed.
Example test_nth_error2 : nth_error [4;5;6;7] 3 = Some 7.
Proof. reflexivity. Qed.
Example test_nth_error3 : nth_error [4;5;6;7] 9 = None.
Proof. reflexivity. Qed.
(In the HTML version, the boilerplate proofs of these
examples are elided. Click on a box if you want to see one.)
This example is also an opportunity to introduce one more small
feature of Coq's programming language: conditional
expressions...
Fixpoint nth_error' (l:natlist) (n:nat) : natoption :=
match l with
| nil ⇒ None
| a :: l' ⇒ if eqb n O then Some a
else nth_error' l' (pred n)
end.
Coq's conditionals are exactly like those found in any other
language, with one small generalization. Since the boolean type
is not built in, Coq actually supports conditional expressions over
any inductively defined type with exactly two constructors. The
guard is considered true if it evaluates to the first constructor
in the Inductive definition and false if it evaluates to the
second.
The function below pulls the nat out of a natoption, returning
a supplied default in the None case.
Definition option_elim (d : nat) (o : natoption) : nat :=
match o with
| Some n' ⇒ n'
| None ⇒ d
end.
Exercise: 2 stars, standard (hd_error)
Using the same idea, fix the hd function from earlier so we don't have to pass a default element for the nil case.Definition hd_error (l : natlist) : natoption
(* REPLACE THIS LINE WITH ":= _your_definition_ ." *). Admitted.
Example test_hd_error1 : hd_error [] = None.
(* FILL IN HERE *) Admitted.
Example test_hd_error2 : hd_error [1] = Some 1.
(* FILL IN HERE *) Admitted.
Example test_hd_error3 : hd_error [5;6] = Some 5.
(* FILL IN HERE *) Admitted.
☐
Exercise: 1 star, standard, optional (option_elim_hd)
This exercise relates your new hd_error to the old hd.Theorem option_elim_hd : ∀ (l:natlist) (default:nat),
hd default l = option_elim default (hd_error l).
Proof.
(* FILL IN HERE *) Admitted.
☐
(* Mon Apr 6 09:16:54 PDT 2020 *)